BRCA 1 & 2 mutations in Sudanese secondary school girls with known breast cancer in their families. - M Elnour, Ahmed; Y Elderdery, Abozer; Mills, Jeremy; Mohammed, Babiker A; Elbiet Abdelaal, Daw; Mohamed, Abdelraheem Osman; Elhassan, Kamal Eldin H; Abdel Wahab, Abdel Hady A; Cooper, Alan (International Journal of Health Sciences, 2012)
Objective: Breast cancer is a major cause of morbidity and mortality as the commonest cancer in women worldwide. In Sudan, it is the most commonly diagnosed cancer. This study assesses the prevalence of BRCA1 and BRCA2 mutations among female students with a family history of breast cancer, in secondary schools of Marawi Locality, Northern State, Sudan. Methods: From a survey of 2370 students, 67 cases were analyzed for BRCA1 and BRCA2 mutations with a single-stranded conformation polymorphism (SSCP) mutation detection method applied to peripheral blood. Eighteen subjects knew of first degree female relatives with breast cancer, 23 with second degree female family members affected and 6 with related male sufferers. Tenty randomly selected girls from the remainder of the survey population with no known family history were also tested. Results: The breast cancer susceptibility genes BRCA1 and BRCA2 accounted, respectively, for 1.21% of responders or 51% of those claiming a family history. Mutations were found in 20% of the group selected with no family history. Only 2 BRCA 2 mutations were found, both in girls with no known afflicted relatives. Six girls knew of male relatives with breast cancer; five of these girls carried mutant BRCA 1. Most of the BRCA1- mutations located to exon 11 fragment 11.9 and 11.1. Conclusion: The study indicates a high prevalence of genetically associated breast cancer in the Marawi locality suggesting a need to focus on the two mutation sites in developing screening protocols for at least this area of Sudan.